- (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The study assesses the contribution of the AFOLU (LULUCF) sector of the Kyrgyz Republic to achieving carbon neutrality by 2050. An inertial business-as-usual (BAU) scenario is used as the baseline; calculations follow IPCC 2006 guidelines. The historical period is 1990–2017, with projections to 2050; the analysis covers forest land and perennial crops on cropland.AFOLU sector provides a persistent natural sink of about 10–11 Mt CO₂-eq yr⁻¹; removals were −10.367 Mt in 2017 and are expected to reach −11.852 Mt by 2050. With BAU-2050 = 45.269 Mt, the gross reduction required for net-zero is ≈33.4 Mt CO₂-eq (−73.8% relative to BAU-2050). The 2030 NDC targets (−15.97%/ −43.62% vs BAU-2030) do not deliver neutrality: the residual net balance is about 10.3 and 3.2 Mt, respectively. The proposed nature-based package—~3.9 thousand ha yr⁻¹ of afforestation/reforestation and ~2.9 thousand ha yr⁻¹ of new perennial plantings—would add ~1.488 Mt CO₂-eq yr⁻¹ of removals by 2050, covering ≈65% of the required increase (~1.49 Mt yr⁻¹).
Keywords: AFOLU, LULUCF, carbon neutrality, BAU, afforestation/reforestation, perennial crops, Kyrgyzstan.